2020
DOI: 10.7554/elife.53706
|View full text |Cite
|
Sign up to set email alerts
|

A moth odorant receptor highly expressed in the ovipositor is involved in detecting host-plant volatiles

Abstract: Antennae are often considered to be the nostrils of insects. Here, we sequenced the transcriptome of the pheromone gland-ovipositor complex of Helicoverpa assulta and discovered that an odorant receptor (OR) gene, HassOR31, had much higher expression in the ovipositor than in antennae or other tissues. To determine whether the ovipositor was involved in odorant detection, we co-expressed HassOR31 and its co-receptor, HassORco, in a Xenopus oocyte model system, and demonstrated that the OR was responsive to 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 48 publications
4
73
0
Order By: Relevance
“…Therefore, we inferred that abdomen cuticles may contain many sensilla, especially on the ovipositor. A recent study showed that HassOR31 highly expressed in ovipositor was involved in detecting host-plant volatiles for determining precise oviposition sites [ 25 ]. This gene may exert a function associated with host-plant volatile detection or stimulation of egg lay.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we inferred that abdomen cuticles may contain many sensilla, especially on the ovipositor. A recent study showed that HassOR31 highly expressed in ovipositor was involved in detecting host-plant volatiles for determining precise oviposition sites [ 25 ]. This gene may exert a function associated with host-plant volatile detection or stimulation of egg lay.…”
Section: Discussionmentioning
confidence: 99%
“…The antennae and the maxillary palps, covered by numerous sensilla, are primary olfactory organs. With the sensilla, the insects can perceive and accurately recognize various odorants from the surrounding environment, which trigger insect behaviors, such as host selection and oviposition decisions [ 3 , 4 , 5 ]. Furthermore, olfaction-based behavioral manipulation has been frequently used for the monitoring and prevention of oriental fruit flies.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study into Helicoverpa assulta found that an odorant receptor gene, HassOR31 which was highly expressed in the ovipositor rather than in antennae, was related to the determination of oviposition in host plants in females. This finding reveals that some ORs located outside the antenna might also have a functional role in vivo ( Li et al, 2020 ). Therefore, further studies are needed to uncover the function of PopeOR3 in the wings of P. operculella .…”
Section: Discussionmentioning
confidence: 85%
“…For example, Bastin-Heline et al (2019) found SlitOR5, a PR from the cotton leafworm Spodoptera littoralis , grouped with a novel PR clade. With a typical structure of seven transmembrane domains, PRs are more abundantly expressed in male antennae ( He et al, 2014 ; Zhang and Löfstedt, 2015 ; Ke et al, 2017 ), whilst some PRs are also found in female antennae and other tissues such as the wings and ovipositor ( Chang et al, 2015 ; Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%